Прецедентний вимір слова І. Котляревського - Сюта, Г. (Культура слова, 2019)
Обґрунтовано статус прецедентних висловлень
І. Котляревського як одиниць сучасного українського мовомислення,
продемонстровано їх актуальність для текстів різних жанрів
(художнього, публіцистичного, інтернет-комунікації). Простежено
текстотвірні, функціонально-стилістичні, комунікативно-
прагматичні, аксіологічні аспекти реінтерпретації цитат,
засвоєних українською мовно-літературною практикою із текстів
поеми «Енеїда» та п’єси «Наталка Полтавка». Продемонстровано
їх актуальність як носіїв лінгвокультурної інформації. Акцентовано
увагу на тому, що афоризовані й потенційно афористичні висловлення
І. Котляревського виконують функцію ментальної консолідації
української поетичної і – в глобальному вимірі – літературної мови. The article deals with the problem of reinterpretation of quotes which
Ukrainian literary language and contemporary Ukrainian communicative
practice adopted from Ivan Kotliarevs’kyj’s texts.
From the point of view of methodology modern interpretation of
Kotliarevs’kyj’s precedent statements envisages the understanding of
national philosophy and intertextual openness of his poetry.
The heuristic value of supervision sabove the using of such quotations
in contemporary language practice is related to their study as active units
of living Ukrainian communication in different functional spheres. That
is why the status of I. Kotlyarevsky’s precedent statements as active
units of modern Ukrainian language is substantiated. Their relevance
for Ukrainian texts of different genres (artistic, journalistic, Internet
communication) is demonstrated. Text-forming, functional-stylistic,
communicative-pragmatic, axiological aspects of the reinterpretation of
quotations, mastered by Ukrainian language-literary practice from the
texts of the poem “Aeneid” and the play “Natalka Poltavka” are traced.
Their relevance as carriers of linguistic and cultural information has been
demonstrated.
It is shown, that Kotlyarevsky’s precedent statements have ability to
separate from the precedent source, acquire some new connotations that
are predefined by a sociocultural or sociopolitical situation.
The aim of this study is to demonstrate that Kotlyarevsky’s precedent
statements are active constructive (from the point of text-building and
content-building) units of modern Ukrainian texts.
The article gives a detailed analysis of contextual pragmatics of
Kotlyarevsky’s intexts. One of the main ideas of this study is to demonstrate
that Kotlyarevsky’s aphoristic and potentially aphoristic statements has a
specific function of mental consolidation of the Ukrainian poetic and – in
the global dimension – literary language.